A disc diffusion assay for detection of class A, B and OXA‐48 carbapenemases in Enterobacteriaceae using phenyl boronic acid, dipicolinic acid and temocillin. (9th August 2013) - van, K.; Voets, G. M.; Scharringa, J.; Voskuil, S.; Fluit, A. C.; Rottier, W. C.; Leverstein‐Van Hall, M. A.; Cohen Stuart, J. W. T.; Cantón, R.
Abstract Class A and B carbapenemases in Enterobacteriaceae may be detected using carbapenemase inhibition tests with boronic acid derivatives (BA) and dipicolinic acid (DPA)/EDTA, respectively. However, for OXA‐48 (like) carbapenemases, no specific inhibitor is available. Because OXA‐48 confers high‐level temocillin resistance, a disc diffusion assay using temocillin as well as BA and DPA inhibition tests was evaluated for detection of class A, B and OXA‐48 carbapenemases. The test collection included 128 well‐characterized non‐repeat Enterobacteriaceae isolates suspected of carbapenemase production; that is, with meropenem MICs ≥ 0.5 mg/L, including 99 carbapenemase producers (36 KPC, one GES, 31 MBL, four KPC plus VIM, 25 OXA‐48, two OXA‐162), and 29 ESBL and/or AmpC‐producing isolates. PCR and sequencing of beta‐lactamase genes was used as a reference test. Phenotypic carbapenemase detection was performed with discs (Rosco) containing meropenem (10 μg), temocillin (30 μg), meropenem + phenyl boronic acid (PBA), meropenem + DPA, meropenem + BA + DPA, and meropenem + cloxacillin (CL). Absence of synergy between meropenem and BA and/or DPA and a temocillin zone ≤10 mm was used to identify OXA‐48. The sensitivity for identification of class A, B and OXA‐48 carbapenemases was 95%, 90% and 100%, with 96–100% specificity. In non‐Proteus species, the sensitivity for class B carbapenemase detection was 97%. All isolates without PBA or DPA synergy and a temocillin disc zone ≤10 mm were OXA‐48 (like) positive. In conclusion, carbapenemase inhibition tests with PBA and DPA combined with a temocillin disc provide a reliable phenotypic confirmation method for class A, B and OXA‐48 carbapenemases in Enterobacteriaceae.